Fire disturbance promotes biodiversity of plants, lichens and birds in the Siberian subarctic tundra - Heim Ramona J; Heim Wieland; Bultmann Helga; Kamp Johannes; Rieker Daniel; Yurtaev Andrey; Holzel Norber (WILEY, 2022)
Fire shapes the world's terrestrial ecosystems and has been influencing biodiversity patterns for millennia. Anthropogenic drivers alter fire regimes. Wildfires can amplify changes in the structure, biodiversity and functioning of the fast-warming tundra ecosystem. However, there is little evidence available, how these fires affect species diversity and community composition of tundra ecosystems over the long term. We studied long-term fire effects on community composition and diversity at different trophic levels of the food web in the subarctic tundra of Western Siberia. In a space-for-time approach we compared three large fire scars (>44, 28 and 12 years old) to unburnt controls. We found that diversity (measured as species richness, Shannon index and evenness) of vascular and non-vascular plants and birds was strongly affected by fire, with the greatest species richness of plants and birds for the intermediate-age fire scar (28 years). Species composition of plants and birds still differed from that of the control >44 years after fire. Increased deciduous shrub cover was related to species richness of all plants in a hump-shaped manner. The proportion of southern (taiga) bird species was highest in the oldest fire scar, which had the highest shrub cover. We conclude that tundra fires have long-term legacies with regard to species diversity and community composition. They may also increase landscape-scale species richness and facilitate range expansions of more southerly distributed species to the subarctic tundra ecosystem.